Calcineurin Regulates Conidiation, Chlamydospore Formation and Virulence in Fusarium oxysporum f. sp. lycopersici - Hou, Yi-Hsuan; Hsu, Li-Hang; Wang, Hsuan-Fu; Lai, Yu-Hsin; Chen, Ying-Lien (Frontiers in Microbiology, 2020)
Fusarium wilt of tomato caused by the ascomycetous fungus Fusarium oxysporum f. sp. lycopersici (Fol) is widespread in most tomato planting areas. Calcineurin is a heterodimeric calcium/calmodulin-dependent protein phosphatase comprised of catalytic (Cna1) and regulatory (Cnb1) subunits. Calcineurin has been studied extensively in human fungal pathogens, but less is known about its roles in plant fungal pathogens. It is known that calcineurin regulates fungal calcium signaling, growth, drug tolerance, and virulence. However, the roles of calcineurin in Fol have not yet been characterized. In this study, we deleted calcineurin CNA1 and CNB1 genes to characterize their roles in conidiation, chlamydospore formation and virulence in Fol. Our results revealed that both cna1 and cnb1 mutants show defects in calcineurin phosphatase activity, vegetative growth and conidiation as compared to the wild type. Furthermore, calcineurin mutants exhibited blunted and swollen hyphae as observed by scanning electron microscopy. Interestingly, we found that Fol calcineurin is critical for chlamydospore formation, a function of calcineurin previously undocumented in the fungal kingdom. According to transcriptome analysis, the expression of 323 and 414 genes was coordinately up- and down-regulated, respectively, in both cna1 and cnb1 mutants. Based on the pathogen infection assay, tomato plants inoculated with cna1 or cnb1 mutant have a dramatic reduction in disease severity, indicating that calcineurin has a vital role in Fol virulence. In conclusion, our findings suggest that Fol calcineurin is required, at least in part, for phosphatase activity, vegetative growth, conidiation, chlamydospore formation and virulence.